Cell-Friendly Chitosan-Xanthan Gum Membranes Incorporating Hydroxyapatite Designed for Periodontal Tissue Regeneration - Rafael Maza Barbosa; Daniel Navarro da Rocha; Renata Francielle Bombaldi de Souza; Jheison Lopes Santos; José Ricardo M. Ferreira; Ângela Maria Moraes (MDPI AG, 2023)
In this work, a simple method was proposed to produce dense composite polysaccharide-based membranes to be used for guided tissue and guided bone regeneration. The mucoadhesive polysaccharides chitosan (C) and xanthan gum (X) were used to produce polyelectrolyte-based complex membranes. Hydroxyapatite (HA) was added to the formulation as a potential drug carrier, in C:X:HA mass proportions equal to 1:1:0.4, 1:1:2, and 1:1:10, and also to improve membranes bioactivity and biomimetic properties. FTIR analysis indicated successful incorporation of HA in the membranes and XRD analysis showed that no changes in the HA crystalline structure were observed after incorporation. The residual mass evaluated by TGA was higher for the formulation produced at the proportion 1:1:10. The membranes produced showed asymmetrical surfaces, with distinct roughness. Increasing the HA concentration increased the surface roughness. Greater in vitro proliferation of dental pulp mesenchymal stem cells was observed on the surface of the membrane with 1:1:10 C:X:HA proportion. However, the 1:1:2 formulation showed the most adequate balance of mechanical and biological properties. These results suggest that adding HA to the membranes can influence mechanical parameters as well as cell adhesion and proliferation, supporting the potential application of these materials in regenerative techniques and the treatment of periodontal lesions.